Mathematical models fof simulation of continuous grinding process with recirculation - Buzáné Kis, Piroska; Mihálykó, Csaba; Lakatos, Béla G. (Acta Cybernetica, 2002)
New mathematical and computer models and simulation programs were elaborated for studying processes of continuous grinding mills working with classification and partial recirculation of the product. The computer models were developed on the basis of the axial dispersion model taking into consideration also the effects of the mixing of the material to be ground. The effects of changes of parameters of both the mill and the material were studied. The stationary states of the continuous grinding mills working with and without classification and recirculation were compared to each other. The mathematical models and the computer programs developed are suitable for computing the processes of the grinding mills either with or without recirculation. They are usable for simulation based analysis and design of both continuous and batch grinding devices.